La gratitud y el tiempo desde el diagnóstico como predictores de la sintomatología depresiva en pacientes oncológicos - Núñez Mondéjar, Jessica Cidia (2019)
This study aimed to explore the extent to which time since diagnosis and gratitude factors predict symptoms of depression in oncological patients. A total of 133 patients at the National Institute of Neoplastic Diseases were evaluated using a convenience sampling method. The Gratitude Scale by Alarcon and the Center for Epidemiologic Studies Depression Scale (CES D) were used for the evaluation. The results revealed that the Sentimental Feature of gratitude is the best predictor of the Depressive Factor b --. t ( 2.50, p and Loss of Interest b --. t ( 2.53, p of the depressive symptomatology. Conversely, time since diagnosis and Moral Duty d o not predict symptoms of depression. Likewise, neither time since diagnosis nor the gratitude factors predict the Diminished Activity of the depressive symptomatology.